Survival of Eclipse Third-party Plug-ins - Businge, John; Serebrenik, Alexander; Brand, Mark van den (International Conference on Software Maintenance (ICSM), 2012)
Today numerous software systems are being developed on top of frameworks. In this study, we analyzed the survival of 467 Eclipse third-party plug-ins altogether having 1,447 versions. We classify these plug-ins into two categories: those that depend on only stable and supported Eclipse APIs and those that depend on at least one of the potentially unstable, discouraged and unsupported Eclipse non-APIs. Comparing the two categories of plug-ins, we observed that the plug-ins depending solely on APIs have a very high source compatibility success rate compared to those that depend on at least one of the non-APIs. However, we have also observed that recently released plug-ins that depend on non-APIs also have a very high forward source compatibility success rate. This high source compatibility success rate is due to the dependency structure of these plug-ins: recently released plug-ins that depend on non-A PIs predominantly depend on old Eclipse non APIs rather than on newly introduced ones. Finally, we showed that the majority of plug-ins hosted on Source Forge do not evolve beyond the first year of release
Keywords: Third-party plug-ins; APIs; non-APIs